Regional institutions managing terrorism and war criminals / Ahmad Lutfee Abdul Razak...[et al.] - Abdul Razak, Ahmad Lutfee; Mohd Faizal, Mohd Amirul Faliq; Sukeri, Muhd Izzat (2012)
Terrorism and war crimes had threatened the lives of many people around the world. The issues had been debated over years, yet the numbers are rapidly growing. Sadly, the management of terrorism and war crimes are not managed efficiently by the responsible bodies. This study examines the needs of human security and global governance and also the weaknesses of the United Nations Organization and Association of Southeast Asian Nations (ASEAN). This project would also highlight the current situations which occur in Middle East and Southeast Asia. Qualitative research methodology is adopted which consists of books, articles and journals. In conclusion, it identifies a need for a better another regional institution to overtake the management of terrorism and war crimes from the United Nations Organization and ASEAN.